Аssessment of the Effectiveness of Etiotropic Prophylaxis of Tick-Borne Infections: the Systematization of concepts and methodological features - N. A. Penyevskaya; N. V. Rudakov (Эпидемиология и вакцинопрофилактика)
This review analyzes the methodological reasons for the heterogeneity of the results of the evaluation of the epidemiological effectiveness of vaccine prophylaxis of tick-borne encephalitis (TBE) using indicators such as the efficiency coefficient (COEF) and the efficiency index (IEF), and their discrepancy  with similar indicators of the immunological effectiveness  of vaccines. It is shown that the calculation of COEF and IEF according to official statistical reporting is illegal in connection with the emergence of systematic errors of selection due to the impossibility of retrospective formation of compared groups of vaccinated and unvaccinated, comparable in risk of infection and disease. In addition, COEF and IEF do not allow to compare the efficiency of vaccination in different areas in physical and monetary units. Based on the analysis of the literature data on immunogenicity of modern vaccines against TBE, protective titer of antibodies and results of field tests of vaccine efficacy in the conditions of total coverage of the population with vaccinations, the authors conclude that the third generation vaccines against TBE protect against disease 95-98% of persons attacked by ticks. Algorithm for calculating the number of preventable cases of TBE diseases is proposed for a comparative evaluation of the effectiveness of vaccination as an anti-epidemic measure in different areas.